2009
DOI: 10.1007/s11237-009-9068-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of structural and thermodynamic factors on the sorption of hydrogen by metal–organic framework compounds

Abstract: UDC 546.03,544.723 S. V. Kolotilov and V. V. PavlishchukThe characteristics of the sorption of hydrogen by metal-organic framework compounds (MOF) were examined, and the structural and thermodynamic factors that favor the sorption of H 2 by such substances were determined. The effect of the structure of the MOF and the size and geometry of the pores on the sorption characteristics was analyzed.The marked worldwide shortage of such sources of natural hydrocarbon fuel as natural gas and petroleum, the need to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 93 publications
3
28
0
Order By: Relevance
“…The assessment of hydrogen density in pores of these compounds at the max imum filling gives values 0.016 and 0.020 g cm -3 for 10 and 11, respectively, and equals 23 and 28% of the hydro gen density at 20 K. These values of H 2 density in pores of the coordination polymers are close to those found earlier. 18 In conclusion, in the present work we found the con ditions for the formation of coordination polymers Fe 2 MO(AcO) 6 (bpy) 1.5 ] n (M = Co, Ni) in the reaction of trinuclear acetate complexes Fe 2 MO(AcO) 6 (H 2 O) 3 with 4,4´ bipyridine. It was shown that the prepared compounds [Fe 2 MO(AcO) 6 (bpy) 1.5 ] n are able to adsorb nitrogen and hydrogen.…”
Section: Resultssupporting
confidence: 59%
“…The assessment of hydrogen density in pores of these compounds at the max imum filling gives values 0.016 and 0.020 g cm -3 for 10 and 11, respectively, and equals 23 and 28% of the hydro gen density at 20 K. These values of H 2 density in pores of the coordination polymers are close to those found earlier. 18 In conclusion, in the present work we found the con ditions for the formation of coordination polymers Fe 2 MO(AcO) 6 (bpy) 1.5 ] n (M = Co, Ni) in the reaction of trinuclear acetate complexes Fe 2 MO(AcO) 6 (H 2 O) 3 with 4,4´ bipyridine. It was shown that the prepared compounds [Fe 2 MO(AcO) 6 (bpy) 1.5 ] n are able to adsorb nitrogen and hydrogen.…”
Section: Resultssupporting
confidence: 59%
“…In the crystal structure of this MOF there are S-shaped channels in which there are coordinated (to the Ni 2+ ions) and uncoordinated water molecules. It was shown by derivatography that the action of heat on NaNi 3 (L13) 2 (OH)(H 2 O) 5 to 350°C leads to the removal of all the water molecules; during dehydration the green color of the complex changes to yellow-brown [indicating changes in the coordination sphere of the nickel(II)], and the surface area increases sharply -the value of S, determined by the sorption of nitrogen, increases from zero (for the undehydrated sample) to 743 m 2 /g and then decreases to 640 m 2 /g for the samples dehydrated at 300 and 350°C respectively [91]. From the order of the signs it is possible to form an opinion about the presence of the coordination-unsaturated nickel ions in the dehydrated form of the complex -in NaNi 3 (L13) 2 (OH)(H 2 O) 5 there are four coordinated molecules of H 2 O for the three nickel ions, and it is unlikely that all the positions in the coordination spheres of the nickel ions will be occupied by donor atoms after dehydration; moreover, rehydration takes place very quickly and is accompanied by a change in the color of the complex.…”
Section: Location Of the Adsorption Centers (Binding Sites) Of H 2 Inmentioning
confidence: 99%
“…From the order of the signs it is possible to form an opinion about the presence of the coordination-unsaturated nickel ions in the dehydrated form of the complex -in NaNi 3 (L13) 2 (OH)(H 2 O) 5 there are four coordinated molecules of H 2 O for the three nickel ions, and it is unlikely that all the positions in the coordination spheres of the nickel ions will be occupied by donor atoms after dehydration; moreover, rehydration takes place very quickly and is accompanied by a change in the color of the complex. Dehydration leads to the formation of the compound NaNi 3 (L13) 2 (OH) (according to calculation from the loss in weight), the structure of which is evidently similar to the structure of NaNi 3 (L13) 2 (OH)(H 2 O) 5 , although it has not been possible to fully interpret the structure of the dehydrated phase [83]. [83] reached a conclusion about bonding of the hydrogen by the coordination-unsaturated nickel ions.…”
Section: Location Of the Adsorption Centers (Binding Sites) Of H 2 Inmentioning
confidence: 99%
See 2 more Smart Citations